Investigation on the Flexural Behaviour of Steel Cold Formed Built up Sections - Preethi, T; Rajkumar, P R Kannan; Jegan, M (International Journal of Integrated Engineering, 2020)
For the past few decades, substantial progress has been made in material properties and construction methodology, which demands in need of development of stronger and lighter members in structural steel applications. The demands of increase in strength and reduction in weight of sections leads to development of structures which are slender and also stability plays a major role in design. The main goal of this study is to develop and investigate the performance of build-up steel I beam sections with corrugated webs. This study focuses on analysis of flexural behaviour and failure modes of plain web, rectangular, trapezoidal web and triangular web in beams by experimental investigations using three point load test and analytical investigations using ANSYS software. From experimental and analytical analysis, triangular corrugated web beam perform better compared to all section. The experimental results obtained are more similar to analytical results obtained by ANSYS software with only slight deviations. The failure modes in both experimental investigation and analytical analysis are similar.